(untitled) (Iranian Journal of Kidney Diseases, 2014)
Screening for hematuria was carried out in 3000 school-age children (6 to14 years old) in Gorgan, Iran, using a fresh morning urine sample. At the initial step, 208 (6.8%) had positive dipstick tests for blood, which decreased to 35 (1.2%) at the second step. Of the 35 children with hematuria, 27 (77.1%) were girls and 8 (22.9%) were boys. Twenty-six children were further evaluated of whom 5 had normal findings, and 7 had hypercalciuria, 13 had nephrolithiasis, and in 1 had a large cystic lesion on ultrasonography, ultimately diagnosed as oncocystoma.